S-nitrosylation of pVHL regulates β 2 adrenergic receptor function - Zachary W. Grimmett; Hiroki Hayashi; Thomas M. Raffay; Justin Lin; Richard T. Premont; Jonathan S. Stamler (Proceedings of the National Academy of Sciences, 2025)
The β 2 -adrenergic receptor (β 2 AR), a prototype G protein–coupled receptor, controls cardiopulmonary function underpinning O 2 delivery. Abundance of the β 2 AR is canonically regulated by G protein–coupled receptor kinases and β-arrestins, but neither controls constitutive receptor levels, which are dependent on ambient O 2 . Basal β 2 AR expression is instead regulated by the prolyl hydroxylase/pVHL-E3 ubiquitin ligase system, explaining O 2 responsivity. Interplay between O 2 and nitric oxide (NO, a potent bronchodilator) is central to cardiopulmonary function. Here, we demonstrate that pVHL-mediated β 2 AR degradation is counteracted by NO, revealing pVHL control of pulmonary function. NO S-nitrosylates Cys77 in human pVHL (cognate to mouse Cys43), which induces binding of the E3 ubiquitin ligase c-Cbl to degrade pVHL, thereby increasing β 2 AR expression. pVHL–C43S mutant mice refractory to S-nitrosylation exhibit decreases in β 2 AR signaling and increases in airway tone. Thus, pVHL controls adrenergic pulmonary function and contributes to bronchodilation by NO. Our findings suggest therapeutic approaches to asthma and obstructive airway disease.